2001
DOI: 10.1093/protein/14.10.815
|View full text |Cite
|
Sign up to set email alerts
|

Optimized linker sequences for the expression of monomeric and dimeric bispecific single-chain diabodies

Abstract: Bispecific single-chain diabodies (scDb) consist of the variable heavy and light chain domains of two antibodies connected by three linkers. The structure of an scDb in the V(H)-V(L) orientation is V(H)A-linkerA-V(L)B-linkerM-V(H)B-linkerB-V(L)A, with linkers A and B routinely chosen to be 5-6 residues and linker M 15-20 residues. Here, we applied display of scDb on filamentous phage to analyse the composition of optimal linker sequences. The three linkers were randomized in length and sequence using degenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 30 publications
1
33
0
Order By: Relevance
“…The diabody preparation contained a contaminant of approximately 35 kDa, similar to that observed by others. 15 Fast protein liquid chromatography (FPLC) analysis (not shown), indicated the diabody to have a solution size of about 50 kDa to 60 kDa, in line with the predicted molecular mass of 54 kDa, and implying that the diabody runs aberrantly on SDS-PAGE. Immunoblotting showed that the diabody bound the MSP1 19 fusion protein ( Figure 1C).…”
Section: Characterization Of Msp1 19 -Specific Human Abs and A Diabodmentioning
confidence: 72%
See 1 more Smart Citation
“…The diabody preparation contained a contaminant of approximately 35 kDa, similar to that observed by others. 15 Fast protein liquid chromatography (FPLC) analysis (not shown), indicated the diabody to have a solution size of about 50 kDa to 60 kDa, in line with the predicted molecular mass of 54 kDa, and implying that the diabody runs aberrantly on SDS-PAGE. Immunoblotting showed that the diabody bound the MSP1 19 fusion protein ( Figure 1C).…”
Section: Characterization Of Msp1 19 -Specific Human Abs and A Diabodmentioning
confidence: 72%
“…First, the VH and VL regions of B10 and M22 were amplified. The 5Ј VH primers incorporated a 5Ј BssHII site in B10 VH and a sequence encoding the C-terminal-half of a 19-residue-"long" linker (RGSGGGGSGGRAGSGGGGS) 15 in M22 VH. The 3Ј primer for both VHs incorporated a sequence encoding a GGGGS linker, 16 whereas the 5Ј VL primers incorporated overlapping GGGGS linkers.…”
Section: Construction Of Expression Vectorsmentioning
confidence: 99%
“…Previous studies suggest that linkers shorter than 12 amino acids can result in multimeric complexes (diabody, triabody, etc.) due to "domain swapping" and that transition between monovalent and divalent scFv can be somewhat controlled by linker length (Atwell et al, 1999;Völkel et al, 2001). Considering these findings, it was our intention to design a predominately monomeric scFv.…”
Section: Discussionmentioning
confidence: 99%
“…due to ''domain swapping,'' and that transition between monovalent and divalent scFv can be somewhat controlled by the linker length. 31,32 Considering these findings, and with the intention of producing a predominately monomeric scFv, we used a 15 amino acid linker to connect the two chains. 10 Source …”
Section: Expression Of Scfv6h4mentioning
confidence: 99%